Effects of omega-3 supplementation associated with physical activity in obese patients with type 2 diabetes mellitus: study protocol - Mário Flávio Cardoso de Lima; Marina Guedes Fraga Lopes; Wellington Henrique Justo Neto; Cláudio Teodoro de Souza (Hospital de Clínicas de Itajubá, 2022)
Objective: This study aims to evaluate the effects of omega-3-rich fish oil supplementation with or without physical activity on anti-inflammatory and insulin resistance parameters in obese and type 2 diabetic individuals. Methods: Randomized, double-blind intervention study of omega-3. Adults with obesity and type 2 diabetes mellitus on exclusive use of metformin as a drug to control blood glucose will be included. The Protocol will be based on clinical and nutritional follow-up (supplementation with omega-3) and remote physical activity for eight weeks. Individuals selected for the study will be randomly assigned to one of the following groups: i) omega-3; ii) omega-3 + physical activity; iii) physical activity + placebo; iv) placebo. To analyze the results, biochemical parameters (fasting glucose and insulin, glycosylated hemoglobin, liver enzymes, urea, creatinine, total cholesterol and fractions, triglycerides, CRP, and ferritin) and inflammatory parameters (TNF alpha, IL-1 beta, IL- 6 and IL-10). At the end of the study, it is expected that the intervention associated with omega-3 in the physical activity protocol will promote a reduction in parameters related to insulin resistance, levels of inflammatory cytokines, and anthropometric parameters.